Applied Agrometeorology - Stigter, Kees.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This compendium first reviews regional operational applications of agrometeorology in the form of case studies of agrometeorological services and information. These services prepare farmers of different income levels for extreme weather and climate events and for the use of weather and climate (3z(Bwindows of opportunity(3y (Bunder conditions of a changing climate. Subsequently wide fields of application are covered such as crops (monocropping and multiple cropping, for which aspects of soils, pests, diseases, water, fertilizers and labour are discussed, in so far as they interact with agrometeorological factors), forestry, agroforestry, livestock, and fisheries. These fields are dealt with in a way that the contents form the bedrock material for establishment, improvement, extension and updating of agrometeorological services and information under these changing conditions. Operational supportive methods are finally reviewed and exemplified through case studies of their applications in the above mentioned fields, in approaches related to actual problem solving in agricultural production. This compendium also wants to create a renaissance in the teaching (that is education/training/ extension) of applied agrometeorology at all levels, closer to the livelihood of farmers and other growers.s
Introductory Part -- Operational applications of agrometeorological services -- Fields of application in agrometeorology -- Methods as tools and approaches successfully used in applications leading to agrometeorological services.
Keywords: Geography; Meteorology; Agriculture; Forests and forestry; Climatic changes; Environmental management; Earth Sciences; Meteorology/Climatology.; Agriculture; Applied Earth Sciences; Environmental Management; Forestry; Climate Change